The impact of mandatory waiting periods on abortion-related outcomes: a synthesis of legal and health evidence - Fiona de Londras; Amanda Cleeve; Maria I. Rodriguez; Alana Farrell; Magdalena Furgalska; Antonella Lavelanet (BMC Public Health, 2022)
Abstract This review follows an established methodology for integrating human rights to address knowledge gaps related to the health and non-health outcomes of mandatory waiting periods (MWPs) for access to abortion. MWP is a requirement imposed by law, policy, or practice, to wait a specified amount of time between requesting and receiving abortion care. Recognizing that MWPs “demean[] women as competent decision-makers”, the World Health Organization recommends against MWPs. International human rights bodies have similarly encouraged states to repeal and not to introduce MWPs, which they recognize as operating as barriers to accessing sexual and reproductive healthcare. This review of 34 studies published between 2010 and 2021, together with international human rights law, establishes the health and non-health harms of MWPs for people seeking abortion, including delayed abortion, opportunity costs, and disproportionate impact. Impacts on abortion providers include increased workloads and system costs.